A comparison of multi‐ligament reconstruction and isolated anterior cruciate ligament reconstruction at one year follow‐up: results from the Danish Knee Ligament Reconstruction Registry - Torsten Grønbech Nielsen; Ole Gade Sørensen; Martin Lind (Journal of Experimental Orthopaedics)
Abstract Introduction The Danish Knee Ligament Reconstruction Registry (DKRR) has monitored the outcomes of surgeries for multi‐ligament knee injuries (MLKI) since 2005. This study aimed to compare the subjective clinical outcomes of patients who had undergone surgery after MLKI with those of patients who had received isolated anterior cruciate ligament (ACL) reconstruction. Materials and methods This study used patient‐reported outcome scores at 1‐year follow‐up as the primary outcome and contains the outcome data of knee ligament surgeries retrieved from the DKRR. Clinical subjective outcomes and knee function were evaluated with Knee Injury and Osteoarthritis Outcome Scores (KOOS) and Tegner Activity Scale (Tegner) scores. Demographic differences were examined using the Student’s t‐test and the chi‐square test. Multiple linear regression was used to analyse the data and adjust for potentially confounding factors. P‐values < 0.05 were considered to be statistically significant. Results A total of 31,686 knee ligament surgeries were registered in the DKRR between 2005 and 2017, resulting in 1,160 multi‐ligament patients and 28,843 isolated ACL patients. The mean age of the MLKI group was significantly higher than that of the isolated ACL group (33.2 years [95% CI 32.5–33.9] vs. 28.3 years [95% CI 28.1–28.4]). The adjusted KOOS Sport and Quality of Life (QoL) sub‐scores and Tegner scores of the MLKI group significantly improved from the baseline to the 1‐year follow‐up (16.7 points [95%CI 12.8;20.6], 12.6 points [95%CI 9.6;15.6] and 1.76 points [95%CI 1.43;2.08], respectively). The KOOS Sport and QoL sub‐scores of the isolated ACL group were significant and increased more than those of the MLKI group. No differences in the Tegner scores were observed. Conclusions Surgical reconstruction after multi‐ligament knee injury resulted in significant subjective outcome improvements at 1‐ year follow‐up. The KOOS Sport and QoL sub‐scores of the isolated ACL group significantly increased compared to those of the MLKI group.